Conceptual approaches to the definition of administrative and legal regulation in the field of anti-bullying in Ukraine - Sobol, Yevhen (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
The article find out that in the modern legal literature there are no specialized scientific developments devoted to administrative and legal regulation in the field of combating bullying in Ukraine. It is noted that this is due to the innovativeness of this phenomenon as a socially negative, the commission of which involves bringing the perpetrators to justice, namely - administrative. It is indicated that the disclosure of the research topic is possible by analyzing such legal categories as «legal regulation», «legal influence» and «administrative and legal regulation». It has been found that in scientific circles two conceptual approaches to the understanding of administrative and legal regulation can be distinguished. In turn, the supporters of the first of them share the position according to which administrative and legal regulation is a kind of legal regulation and is a purposeful influence of administrative law on public relations in order to ensure the rights and legitimate interests of man and citizen. Regarding the second approach, its content is reduced to the understanding of the administrative and legal regulation of the imperative and normative regulation of public relations in order to ensure the interests of the state. The analysis of conceptual approaches to the definition of administrative and legal regulation allowed to form the author's vision of the concept of administrative and legal regulation in the field of bullying, which should be understood as purposeful, orderly-organizational, systemic, power-administrative influence of the state in the face of authorized subjects. arising in the learning environment between their participants, which is carried out through the implementation of administrative law to ensure the rights, freedoms and legitimate interests of man and citizen in general, as well as participants in this learning environment in particular, and aimed at counteracting socially negative phenomena - bullying.